Peran Pelatihan dalam Meningkatkan Kinerja Karyawan PT. Sinergi Persada Nusantara - Adam Wahyu Satrio; Suroso Suroso; Dwi Epty Hidayaty (Journal of Management and Creative Business, 2026)
The purpose of this study is to determine the role of training in improving employee performance at PT. Sinergi Persada Nusantara. This study design uses a qualitative research method with data collection techniques through in-depth interviews, observation, and documentation of informants in the company environment of PT. Sinergi Persada Nusantara office. The results of the study indicate that the implementation of employee training programs has a significant influence on improving employee performance. Employees feel more appreciated and have higher work enthusiasm due to training and competency development from the company, supporting factors have a very important role in ensuring that training results can be applied effectively by employees in their daily work, this program helps improve technical skills and understanding of company values. As a result, employees show an increase in work efficiency, discipline, and sense of responsibility. The implications are that employee training leads to improved organizational competence and performance, as it makes employees more effective, disciplined, and motivated, thereby enabling the company to more easily achieve its goals and enhance its competitiveness; therefore, it should be viewed as a long-term investment.